Data for paper "From One Pattern into Another: Analysis of Turing Patterns in Heterogeneous Domains via WKBJ" - Krause, A; Gaffney, E (University of Oxford, 2019)
All Figures were created via Matlab, COMSOL, and Mathematica as described in the paper, and CSV/TSV files are included for all raw data.